Diversity‐Oriented Synthesis of Natural‐Product‐like Libraries Containing a 3‐Methylbenzofuran Moiety for the Discovery of New Chemical Elicitors. Issue 1 (9th December 2016) - He, Xingrui; Chen, Xia; Lin, Songbo; Mo, Xiaochang; Zhou, Pengyong; Zhang, Zhihao; Lu, Yaoyao; Yang, Yu; Gu, Haining; Shang, Zhicai; Lou, Yonggen; Wu, Jun
Abstract: Natural products are a major source of biological molecules. The 3‐methylfuran scaffold is found in a variety of plant secondary metabolite chemical elicitors that confer host‐plant resistance against insect pests. Herein, the diversity‐oriented synthesis of a natural‐product‐like library is reported, in which the 3‐methylfuran core is fused in an angular attachment to six common natural product scaffolds—coumarin, chalcone, flavone, flavonol, isoflavone and isoquinolinone. The structural diversity of this library is assessed computationally using cheminformatic analysis. Phenotypic high‐throughput screening of β‐glucuronidase activity uncovers several hits. Further in vivo screening confirms that these hits can induce resistance in rice to nymphs of the brown planthopper Nilaparvata lugens . This work validates the combination of diversity‐oriented synthesis and high‐throughput screening of β‐glucuronidase activity as a strategy for discovering new chemical elicitors. Abstract : Natural‐product‐like libraries : Coumarin, chalcone, flavone, flavonol, isoflavone and isoquinolinone are six naturally occurring compounds that are ubiquitous in diverse plants. To extend molecular diversity and discover chemical elicitors, the diversity‐oriented synthesis is reported of a natural‐product‐like library, in which the 3‐methylfuran core is fused to the six common natural product scaffolds.